PENGEMBANGAN MATA KULIAH HADIS TARBAWI PADA PERGURUAN TINGGI ISLAM - Nawas, M Zuhri Abu; Sapruddin, Sapruddin (Jurnal Studi Agama dan Masyarakat, 2020)
The Tarbawi Hadith material development is a study carried out in the framework of development and component results and approach analysis. This included the development of tarbawi hadith course accessed by integrating and interconnecting science. This research provided inspiration and innovation in the development of constructive scientific quality and presenting reinforcement of learning formulation material as a scientific study program. This